Open water - Nelson, Caleb Azumah (Black Cat, 2021)
"In a crowded London pub, two young people meet. Both are Black British, both won scholarships to private schools where they struggled to belong, both are now artists--he a photographer, she a dancer--and both are trying to make their mark in a world that by turns celebrates and rejects them. Tentatively, tenderly, they fall in love. But two people who seem destined to be together can still be torn apart by fear and violence, and over the course of a year they find their relationship tested by forces beyond their control. Narrated with deep intimacy, Open Water is at once an achingly beautiful love story and a potent insight into race and masculinity that asks what it means to be a person in a world that sees you only as a Black body; to be vulnerable when you are only respected for strength; to find safety in love, only to lose it. With gorgeous, soulful intensity, and blistering emotional intelligence, Caleb Azumah Nelson gives a profoundly sensitive portrait of romantic love in all its feverish waves and comforting beauty. This is one of the most essential debut novels of recent years, heralding the arrival of a stellar and prodigious young talent"--